Estimation of Fishing Mortality Rate and Exploitation Status of Yellowstrip Scad (Selaroides leptolepis) in Tomini Bay using Von Bertalanffy Growth Model Approach - Nuralim Pasisingi; Faizal Kasim; Zulkifli Arsalam MoO (Jurnal Ilmiah Perikanan dan Kelautan, 2021)
Highlight ResearchThe fishing area of S. leptolepis in this study was confirmed to be located in Tomini BayThe fish samples were gathered randomly from fishers' catch using purse seinesThe growth curve for the male and female fish data were both plotted following the trend of the Von Bertalanffy equationThis study estimates the growth parameters, mortality, and exploitation rates of the male and female fish separately.AbstractComprehensive data is required for implementing sustainable fisheries management. Population dynamic and stock assessment aspects of Selaroides leptolepis species in Tomini Bay have not been entirely reported. This study aimed to determine the fishing mortality rate and exploitation status of S. leptolepis in Tomini Bay by calculating Von Bertalanffy growth model parameters (Lâˆž, K, t0) then plotting them into Pauly's empirical equation. The sampling was conducted monthly from April to September 2020 at Gorontalo City Fishing Port. Samples were collected randomly from five commercial fishing vessels shortly after the fishermen landed their catch at the fishing port. All fish samples were confirmed to be obtained by the fishermen from Tomini waters. The growth parameters of the samples were analyzed using FiSAT II based on Von Bertalanffy mathematical model. While the mortality and exploitation values were calculated manually using Pauly's equation. The study showed that the growth parameter values of S. leptolepis in Tomini Bay were 245.47 mm, 0.49/year, and -3.04/year for males, while 227.80 mm, 0.63/year, and -2.72/year for females separately for Lâˆž, K, and t0. The total, natural, and fishing mortality rates were 3.06/year, 0.61/year, and 2.45/year for males and 0.99/year, 0.74/year, and 0.25/year for females. The analysis results showed that the female's natural mortality (M) was higher than the male. In contrast, the fishing mortality (F) and total mortality (Z) of male fish exceed the female. The exploitation value of males (E=0.80) was greater than that of females (E=0.26).